Nonlinear Dynamics, Volume 2 Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014 - Kerschen, Gaetan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This critical collection examines a range of nonlinear dynamics, from nonlinear modal analysis to nonlinear systems to nonlinear modeling & simulation, as presented in early findings and case studies from the Proceedings of the 32nd IMAC, A Conference and Exposition on Structural Dynamics, 2014. The collection includes papers in the following general technical research areas:  ·         Nonlinear Oscillations ·         Nonlinear Simulation Using Harmonic Balance ·         Nonlinear Modal Analysis ·         Nonlinear System Identification ·         Nonlinear Modeling & Simulation ·         Nonlinearity in Practice ·         Nonlinear Systems ·         Round Robin on Nonlinear System Identification.
Co-existing Responses in a Harmonically-excited Nonlinear Structural System -- Complex Behavior of a Buckled Beam Under Combined Harmonic and Random Loading -- The Harmonic Balance Method for Advanced Analysis and Design of Nonlinear Mechanical Systems -- A Framework for the Computational Dynamic Analysis of Coupled Structures Using Nonlinear Modes -- Model Updating of Nonlinear Structures -- Detection of Nonlinear Behaviour of Composite Components Before and After Endurance Trials -- Nonlinear Time Series Analysis Using Bayesian Mixture of Experts -- Identifying Robust Subspaces for Dynamically Consistent Reduced-Order Models -- Identification of Sub and Higher Harmonic Vibrations in Vibro-Impact Systems -- An Efficient Simulation Method for Structures With Local Nonlinearity -- Parametric Nonlinearity Identification of a Gearbox From Measured Frequency Response Data -- Nonlinear Gear Transmission System Numerical Dynamic Analysis and Experimental Validation -- A Stochastic Framework for Subspace Identification of a Strongly Nonlinear Aerospace Structure -- Identification of Agricultural Tyres’ Handling Characteristics From Full Scale Experimental Tests -- Nonparametric Analysis and Nonlinear State-space Identification: A Benchmark Example -- Nonlinear Black-box Identification of a Mechanical Benchmark System -- Suppression of Multiple Order Friction Torque Fluctuations With Modulated Actuation Pressure -- Nonlinear Structural Coupling -- Experimental Application -- State Estimation in Nonlinear Structural Systems -- An Efficient Exponential Integrator for Large Stiff Systems: Part 1: Theoretical Investigation -- An Efficient Exponential Integrator for Large Stiff System: Part 2: Symplecticity and Global Error Analysis -- Vibration Suppression of a Flexible Parallel Kinematic Manipulator -- Analysis of Nonlinear System Response to an Impulse Excitation -- Experimental Evaluation of Veering Crossing and Lock-in Occurring in Parameter Varying Systems.
Keywords: Vibration; Dynamical systems; Dynamics; Statistical physics; Mechanics; Mechanics, Applied; Vibration, Dynamical Systems, Control; Applications of Nonlinear Dynamics and Chaos Theory; Solid Mechanics